2006
DOI: 10.1002/lsm.20302
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence staining of human ovarian cancer tissue following application of 5‐aminolevulinic acid: Fluorescence microscopy studies

Abstract: On a microscopic scale, ALA-induced PP IX fluorescence is confined to ovarian cancer tumor tissue sparing stromal tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
15
0
3
Order By: Relevance
“…A recent randomized multicentre phase III trial demonstrated that fluorescence-guided resection of malignant gliomas using 5 ALAinduced porphyrins enables more complete resections of contrast-enhancing tumor and leads to an improved progression-free survival [10]. The clinical usefulness of 5-ALA guided detection of tumor tissue has also been demonstrated for bladder cancer [11][12][13], malignancies of the oral cavity [14,15] and the lung [16], the female genital tract [17,18], intraperitoneal metastases [19,20] the gastrointestinal mucosa [21] and skin [22]. However, current techniques of intraoperative detection of PpIX fluorescence do not offer subcellular resolution.…”
Section: -Aminolevulinic Acid (5-ala) Is a Naturally Occurring Intermentioning
confidence: 99%
“…A recent randomized multicentre phase III trial demonstrated that fluorescence-guided resection of malignant gliomas using 5 ALAinduced porphyrins enables more complete resections of contrast-enhancing tumor and leads to an improved progression-free survival [10]. The clinical usefulness of 5-ALA guided detection of tumor tissue has also been demonstrated for bladder cancer [11][12][13], malignancies of the oral cavity [14,15] and the lung [16], the female genital tract [17,18], intraperitoneal metastases [19,20] the gastrointestinal mucosa [21] and skin [22]. However, current techniques of intraoperative detection of PpIX fluorescence do not offer subcellular resolution.…”
Section: -Aminolevulinic Acid (5-ala) Is a Naturally Occurring Intermentioning
confidence: 99%
“…Loning et al [22] showed in human ovarian cancer that conversion of the potent photosensitizer PpIX from 5-ALA is specific for intra peritoneal (i.p.) ovarian micrometastasis.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] In addition to ICG, there is extensive ongoing research using fluorescein and 5-aminolevulinic acid-induced protoporphyrin IX (PpIX) imaging for neurosurgery, [17][18][19][20][21] a procedure that has gained clinical approval in a handful of countries (Approved by the European Medicines Agency in September 2007 and is approved for use in all European Union, European Economic Area, and European Free Trade Association states). Additionally, PpIX fluorescence imaging using blue light illumination has local approvals in some countries for subspecialty use in bladder cancer detection [22][23][24] and gynecologic oncology [25][26][27] with clinical trials underway. These fluorophores are FDA approved for certain indications and emit fluorescence within the visible light range; therefore, existing surgical microscopes can be modified with some basic filters to allow surgeons to switch back and forth between white-light and fluorescence modes.…”
Section: Introductionmentioning
confidence: 99%